The Great political theories - Curtis, Michael 1923- (HarperPerennial ModernClassics, 2008)
Introduced political ideas from Sophocles and Plato to Locke and Montesquieu in vol. 1 and from Burke, Rousseau and Kant to modern times in vol. 2.